Wizje estetyczne S. Załygina, W. Astafjewa i W. Rasputina (na materiale publicystyki) - Kamiński, Piotr (Studia Rossica Posnaniensia, 2011)
During the analysis basic affinity of aesthetic systems of S. Zalygin, V. Astaf 'ev and V. Rasputin comes to light. Aesthetics of three writers is determined by their ethics. Ethics determine sights of writers on applicability of art (literature), representation about mission of the artist to a society. For writers the sight on the literature, as on national and moral consciousness of people is characteristic.